Simultaneous EEG‐fMRI Reveals a Visual Working Memory Encoding Network Related to Theta Oscillatory Activity in Healthy Subjects - Leicht, Gregor; Rauh, Jonas; Mußmann, Marius; Vauth, Sebastian; Steinmann, Saskia; Haaf, Moritz; Haenschel, Corinna; Mulert, Christoph (Human brain mapping, 2025)
ABSTRACT Working memory (WM) is crucially involved in many aspects of higher cognitive functions and goal‐directed behavior. The encoding of sensory information necessitates the conversion of sensory stimuli into maintainable constructs. Oscillatory activity in the theta frequency range (4–8 Hz) of the human electroencephalogram (EEG) has been related to this. However, so far, no study has investigated the neurophysiological mechanisms and the brain network structure underlying the WM encoding process simultaneously. Thus, this study aimed to test whether theta oscillatory activity would be specifically related to the activity within a WM encoding brain network in healthy subjects by means of simultaneous recordings of EEG and functional magnetic resonance imaging (fMRI). Simultaneous recordings of EEG and fMRI were conducted in 32 healthy subjects during the performance of a visual working memory delayed matched to sample task. The fMRI analysis was informed by single‐trial theta oscillatory responses to encoding stimuli. This analysis revealed a working memory encoding network mediated by theta oscillatory activity. The network included regions within the dorsolateral prefrontal cortex and parietal areas. Our results give reason to assume that the formation of a working memory network might take place during the encoding of information utilizing theta synchrony as a binding mechanism. By means of simultaneous recordings of EEG and fMRI, we identified a working memory encoding network mediated by theta oscillatory activity, including the dorsolateral prefrontal cortex and parietal areas. Our results suggest the formation of such a network during the encoding phase, possibly utilizing theta synchrony as a binding mechanism.